Investigating the link between financial dollarization and inflation : evidence from Jamaica - Bailey, Sherene A. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Provides a descriptive analysis of the factors influencing the evolution of financial dollarization in Jamaica.